Contributions of Scholars of District Haripur in Research and Publications (Part: 1) - Muhammad Ikramullah; Junaid Akbar (Journal of Islamic and Religious Studies, 2018)
If you have a relationship with the past, a sustainable plan can be done for future. Islamic personalities, especially the introduction of the scholars, intensify the path of progress in the field of scientific and research as well as the continuous hard work in the practical world. Similarly, when introduction of the people with historical roles have reached to the next generation, it is easy to define pathways and take lessons from the opponents to work hard for them. Introducing individuals with a specific region is worth a king's ransom investment for all its geographically entrusted and external roles and a leading rule for a new generation of races. In the underlying article, efforts are being made to present brief introduction of the scholars of the District Haripur who have written in various sciences and fictions, so that people of this region can know that this area also remained the base of Islamic scholars. Due to this article, depicting the introduction of the scholars of different school of thoughts will undermine an enormous and sectarian ideology, and the strength of tolerance and brotherhood will be strengthened.